Not all systematic reviews are systematic: a meta-review of the quality of systematic reviews for non-invasive remote monitoring in heart failure. (September 2013) - Conway, Aaron; Inglis, Sally C; Chang, Anne M; Horton-Breshears, Margaret; Cleland, John GF; Clark, Robyn A
We carried out a critical appraisal and synthesis of the systematic reviews and meta-analyses of remote monitoring for heart failure. A comprehensive literature search identified 65 relevant publications from 3333 citations. Seventeen studies fulfilled the inclusion and exclusion criteria. Seven (41%) systematic reviews pooled results for meta-analysis. Eight (47%) considered all non-invasive remote monitoring strategies. Five (29%) focused on telemonitoring. Four (24%) included both non-invasive and invasive technologies. The reviews were appraised by two independent reviewers for their quality and risk of bias using the AMSTAR tool. According to the AMSTAR criteria, ten (58%) systematic reviews were of poor methodological quality. In the high quality reviews, the relative risk of mortality in patients who received remote monitoring ranged from 0.53 to 0.88. The high quality reviews also reported that remote monitoring reduced the relative risk of all-cause (0.52 to 0.96) and heart failure-related hospitalizations (0.72 to 0.79) and, as a consequence, healthcare costs. However, further research is required before considering widespread implementation of remote monitoring. The subset of the heart failure population that derives the most benefit from intensive monitoring, the best technology, and the optimum duration of monitoring, all need to be identified.